DEVELOPING INSTRUCTIONAL VIDEO USING WONDERSHARE FILMORA 9 IN THE CRITICAL READING COURSE FOR STUDENTS OF ENGLISH LANGUAGE EDUCATION DWIJENDRA UNIVERSITY - Ni Made Yuniari; I Gusti Ayu Indah Triana Juliari; I Putu Yudi Sudarmawan (Language and Education Journal Undiksha, 2022)
This study aimed at developing instructional video using Wondershare Filmora 9 in the Critical Reading course for forth semester students of English Language Education Dwijendra University. The research design used in this study was R&D method by using ADDIE model. This model have five stages development, namely: analysis, design, development, implementation, and evaluation. This study used questionnaire as a research instrument. The questionnaires were used to determine the feasibility level of instructional video. In analyzing the data, this study followed some procedures, such as: analyzing the needs, analyzing materials, determining basic competencies and indicators. This study used two validators for checking the materials and others two validators were for learning media expert. Based on the result of the study, it showed that the percentage of the material expert I was 91%, and the validation results from the material expert 2 was 94%. Then, the average from the two materials experts were 92,31%. It means the category of qualitative is very good based on education criteria. Meanwhile, the percentage of media expert I validation was 88,24%, while the validation results from the media expert II was 84,71%. The average of the media experts were 93.84%. It could be said as a good qualities according to reviews from learning content experts. Therefore, it could be concluded that the instructional videos that were created with Wondershare Filmora's 9 becomes an excellent choice to be used for critical reading course.